Analisis Cost-Volume-Profit (CVP) dan Break Even Point untuk Menentukan Strategi Penjualan pada Kaleela Chocolate Fountain - Toto Sudianto; Firyaliza Dwi Putri; Restu Fahrezi; Ahmad Rifai Lubis (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study aims to analyze Cost-Volume-Profit (CVP) and Break Even Point (BEP) as a basis for determining sales strategies at Kaleela Chocolate Fountain. A quantitative descriptive method was employed using sales, fixed cost, variable cost, and profit data from January to May 2026. The analysis included the calculation of Contribution Margin (CM), Contribution Margin Ratio (CMR), Break Even Point (BEP), Margin of Safety (MOS), and target sales. The results indicate that the CMR ranged from 32.51% to 45.69%, while the required sales target to achieve an average monthly profit of IDR 7,400,200 ranged from IDR 17,161,336 to IDR 24,119,457. Actual sales met the target only in January and February. Therefore, the recommended strategies include strengthening digital marketing, expanding collaboration with Wedding Organizers and Event Organizers, controlling variable costs, and offering promotional packages to improve sales volume and profitability.